THE LIVER AS THE SITE OF C-REACTIVE PROTEIN FORMATION - Hurlimann, J. (The Rockefeller University Press, 1966)
The site of formation of C-reactive protein (CxRP, CRP) has been studied with tissues from rabbits, monkeys, and human beings. Rabbits and monkeys were stimulated to produce the acute phase protein by injection of turpentine, croton oil, endotoxin, paratyphoid-typhoid vaccine, or pneumococci. C(14)-amino acid incorporation in vitro was demonstrated by means of autoradiography of immunoelectrophoretic patterns made with culture fluids. It was found that among many different tissues tested liver was the only tissue which incorporated C(14)-lysine and isoleucine into CxRP or CRP. Only livers taken 16 to 24 hr after various stimuli were active; livers from normal animals or from animals killed 3 to 9 hr after stimulation did not produce detectable amounts of CxRP. Inflamed muscle from the injection site did not show C(14)-amino acid incorporation into CxRP. Several human tissues were also cultured, and a few liver cultures found to contain labeled CRP. The formation of CxRP or CRP by the liver was always accompanied by enhanced C(14)-amino acid incorporation into other serum proteins, but the reverse was not always found.